Keraring Intrastromal Segment Depth Measured by Spectral-Domain Optical Coherence Tomography in Eyes with Keratoconus - Ugo de Sanctis; Carlo Lavia; Marco Nassisi; Savino D’Amelio (Journal of Ophthalmology)
Purpose. To evaluate agreement between measured and intended distance of Keraring (Mediphacos, Belo Horizonte, Brazil) intracorneal ring segments from the anterior and posterior corneal surfaces. Methods. Twenty-six Keraring ICRS implanted in 24 keratoconic eyes were examined. The distance from the Keraring apex to the anterior corneal surface and the distance from the inner and the outer corners to the posterior corneal surface were measured 3 months postoperatively using spectral-domain optical coherence tomography. Agreement between measured distance and intended distance was assessed by calculating the absolute differences and 95% limits of agreement (95% LoA). Results. The mean absolute difference was significantly lower (p<0.001) for the measurements taken at the inner corner (23.54±15.90 μm) than that for those taken at the apex (108.92±62.72 μm) and the outer corner (108.35±56.99 μm). The measurements taken at the inner corner were within ±25 and ±50 μm of the intended distance in 15/26 (57.7%) and 24/26 (92.3%) cases, respectively, and showed the narrowest 95% LoA with the intended distance (−57.61 to 55.15 μm). Conclusions. The distance of the inner corner from the posterior corneal surface showed the best agreement with the intended distance. This measurement is suitable for determining whether the actual Keraring depth matches the intended depth.